A CROSSROADS IN MANAGING SOCIAL INTERVENTION AT TWO LEVEL OF PRACTICE: LESSON LEARNED FROM COMMUNITY ENGAGEMENT IMPLEMENTATION - Annisah, Annisah; Agus, Anna Amalyah; Ramzy, Fardhan Zaka; Machdum, Sari Viciawati (Jurnal Penelitian Kesejahteraan Sosial, 2020)
The complexity of health problems in society cannot be viewed partially. The process of social intervention needs to get studied from a variety of perspectives and synergize with various parties. The development of comprehensive and integrated social interventions with the stakeholders has various challenges, especially in the social interventions that involve nutritional needs problems for low-income families. Through action research conducted in Sawangan Baru Village from 2017 until 2018, these challenges are real but can be solved easily. The 26 participants consisting of doctors, midwives, nutritionists, village officials, NGOs, community health worker (kader), beneficiaries, and academics, were very supportive and made the barriers in the social intervention are well managed. The research results showed that in an implementation of social interventions in the community level, social workers need to be flexible in applying the three levels of intervention and using various relevant theories as reference. The focus of research is on practice within the scope of the group (mezzo) level but used a variety of practices and theories in its implementation, that are often applied in the individual (micro) level. Moreover, this research also connected individual needs with resources on the broader community and environment (macro). The author argues that behavioral changing in the individual level is one of the keys to success in attempts to overcome complex health problems.